1983
DOI: 10.3181/00379727-172-41566
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes in Rat Liver after 18.5 Days of Spaceflight

Abstract: The effect of "weightlessness" on liver metabolism was examined using tissue from rats flown in earth orbit for 18.5 days aboard the Soviet Cosmos 936 biosatellite. Changes in the activities of certain carbohydrate and lipid enzymes were noted. Of the 28 hepatic enzyme activities assayed, two, palmitoyl-CoA desaturase and lactate dehydrogenase, increased, whereas five, glycogen phosphorylase, 6-phosphogluconate dehydrogenase, both acyltransferases which act on a-glycerolphosphate and diglycerides, and aconitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(2) investigated hepatic biochemical changes in rats flown aboard the Cosmos 690, 936, and 1129 biosatellite missions. At landing, hepatic glycogen content increased by ϳ30-70% above ground-based controls (1,2,36); accumulation of fat droplets in hepatocytes was also noted (29). These findings were later supported by data collected from rats flown aboard the Cosmos 2044 and 1887 as well as the Spacelab 3 missions (29,30).…”
mentioning
confidence: 61%
“…(2) investigated hepatic biochemical changes in rats flown aboard the Cosmos 690, 936, and 1129 biosatellite missions. At landing, hepatic glycogen content increased by ϳ30-70% above ground-based controls (1,2,36); accumulation of fat droplets in hepatocytes was also noted (29). These findings were later supported by data collected from rats flown aboard the Cosmos 2044 and 1887 as well as the Spacelab 3 missions (29,30).…”
mentioning
confidence: 61%
“…Long stays in microgravity do not represent an intensive stressogenic stimulus for endocrine organs; and hormone alterations observed after spaceflight are suggested to be due primarily to acute stressor activity resulting from the return to Earth's gravity 16 . Activities of seven out of 28 enzymes in rat liver examined indicated changes characteristic of 18.5 day spaceflight compared with centrifuged rats 17 . These suggest that certain hepatic enzyme activities, including CYP, are more sensitive markers of microgravity than hormonal changes.…”
Section: Discussionmentioning
confidence: 85%
“…Studies in rats during space flights, in which blood is possibly translocated (Hoffler 1971;Grounds 1979), have shown that the activity of many hepatic enzymes is profoundly modified (Abrahams et al 1983), Whether these effects are related to ANF remains to be determined.…”
Section: Discussionmentioning
confidence: 99%